The relationship between emotional intelligence and organizational commitment among nurses working in governmental hospitals in Jordan - Islam Al-Oweidat; Ghada Abu Shosha; Tasneem Abu Baker; Abdulqadir J. Nashwan (BMC, 2023)
Abstract Introduction Nurses' emotions and feelings in response to their environment and their ability to manage their emotions can significantly affect several aspects of their job. In Jordan, studies are still investigating whether emotional intelligence is significantly related to organizational commitment. Aim To investigate whether a significant relationship exists between emotional intelligence and organizational commitment among Jordanian nurses working in governmental hospitals in Jordan. Methods The study used a descriptive cross-sectional correlational design. A convenience sampling method was used to recruit participants working in governmental hospitals. A total of 200 nurses participated in the study. A participant information sheet developed by the researcher was used to obtain the participants' socio-demographic characteristics, the Emotional Intelligence Scale (EIS) developed by Schutte and colleagues, and the Organizational Commitment Scale developed by Meyer and Allen were utilized for data collection. Results Participants had high levels of emotional intelligence (M, SD = 122.3, 14.0) and moderate levels of organizational commitment (M, SD = 81.6, 15.7). Emotional intelligence had a significant, positive relationship with organizational commitment (r = 0.53, p < 0.01). Male nurses, widowed nurses, and nurses with higher postgraduate qualifications demonstrated significantly higher levels of emotional intelligence and organizational commitment than female nurses, single nurses, and nurses with undergraduate degrees (p < 0.05). Conclusion Participants in the current study were highly emotionally intelligent and moderately committed to their organizations. Policies supporting the implementation of interventions to improve organizational commitment and maintain a high level of emotional intelligence should be developed and promoted by nurse managers and hospital administrators, as well as decision-makers should magnet the nurses with postgraduate degrees at clinical sites.